GAMBARAN TINGKAT PENGETAHUAN SIWA SMA TENTANG PERTOLONGAN PERTAMA CEDERA OLAHRAGA DI SMA SWASTA RK DELI MURNI DISKI TAHUN 2024 - Indra Hizkia Perangin angin; Magda Siringo-ringo; Clara br raja guk guk (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Background: Sports injury as an injury that occurs during sports activities caused by technical errors, physical pressure, collisions so that first aid must be given, knowledge in first aid is very necessary in order to be able to help someone who has a sports injury. Objective: To find out the level of knowledge of high school students about first aid for sports injuries. Methods: This study uses a descriptive method where this study uses a questionnaire with a total research population of 137 people, with a sample of 58 respondents with a total sampling data collection technique. The data analysis technique used is univariate analysis. This research was conducted at RK Deli Murni Diski Private High School on April 29 - May 05, 2024. Results: In the category of understanding and various types of injuries, good results are obtained, namely 52 respondents (89.7%), the category of how to provide sports injury assistance obtained results, namely less than 58 respondents (100%) and the category of sports injury assistance with a sufficient category of 37 respondents (63.8%) so that the level of knowledge of RK Deli Murni Diski Private High School students was included in the good category as many as 41 respondents (70.7%). Conclusion: The level of knowledge students is in the good category. Suggestion: It is hoped that there will be an increase in health education about sports injury relief carried out by health workers and teachers by conducting special training and providing health education or training in providing first aid to sports injuries at RK Deli Murni Diski Private High School